Influence of an empirical Geological Strength Index method for determining linear and nonlinear failure criteria - Avendaño, Eslainer; Vivanco, Angelica (Wroclaw University of Technology, 2024)
The construction of tunnels and underground galleries in mining has as fundamental input data the results of the failure criteria: traditionally Hoek–Brown and Mohr–Coulomb, to determine the failure envelopes that will allow the design of an economically exploitable mining system within viable safety frameworks that these criteria will guide. Therefore, the determination of rock mass resistance becomes fundamental and complex simultaneously due to the very nature of rock mass. Then, to identify a stressful state in which an excavation can be in conditions of stability it is necessary to have certain information both high in quality and economically valuable, which is not available in the early stages of the mining project. Thus, empirical methods and statistical relationships take notoriety, so this research evaluates the influence of an empirical method for the determination of the Geological Strength Index on the Mohr–Coulomb and Hoek–Brown failure criteria, with the benefit of estimating a stress field in which the exca-vation can self-sustain, evaluated in a first estimate in the pre-feasibility stage of the project, giving a guideline for design engineers. This research argues that the Geological Strength Index estimation method of Vivanco and Avendaño is recommended to estimate the Mohr–Coulomb failure criterion, but not the Hoek–Brown failure criterion.
Mining Science, Vol. 31, 2024, s. 199-218
Keywords: mining; geology; geo-engineering